Original paperThe use of an interstitial boost in the conservative treatment of breast cancer: how to perform it routinely in a radiotherapy department - Gutiérrez, Cristina; Najjari, Dina; Martínez, Evelyn; Botella, Saray; Eraso, Arantxa; Pino, Francisco; Moreno, Ferran; Pera, Joan; Guedea, Ferran (Journal of Contemporary Brachytherapy, 2014)
Purpose: To demonstrate the utility of a boost with interstitial brachytherapy (BT) in breast-conserving therapy (BCT) by doing a thorough review of the literature and describing in detail our technique for delivering this boost. Material and methods: Our department has been delivering the boost with interstitial BT since 1989, in most cases with rigid needles and a theoretical dosimetry. In the early years, we used low-dose-rate (LDR) with iridium-192 wires. The dose administered was 15 Gy if there were no risk factors for local relapse or 20-25 Gy in the presence of risk factors. The risk factors considered were the presence of a close margin (less than 10 mm) and an extensive intraductal component (more than 25%). After 2002, we switched to high-dose-rate (HDR); using the linear quadratic model we changed the low dose to 3 fractions of 4.5 Gy in the case of no risk factors for local relapse or to 3 fractions of 5 Gy in the presence of risk factors. Results : In 79 consecutive boost patients treated in our department between 2010 and 2011, with a median follow-up of 46 months, the local control rate was 97.47%. With respect to cosmesis, fibrosis occurred in 17 cases (21.5%) and hyperpigmentation in 26 cases (32.9%). Our hospital’s results are comparable in terms of local control and cosmesis to those of other authors. Conclusions : This educational article describes our department’s boost technique with rigid needles and comments briefly on our results using this technique in a group of consecutively treated patients in our department. A review of the literature and the published results on local control and cosmesis is also described.